Role of ternary hybrid nanofluid in the thermal distribution of a dovetail fin with the internal generation of heat - Goud, J Suresh; Srilatha, Pudhari; Varun Kumar, R.S.; Kumar, K. Thanesh; Khan, Umair; Raizah, Zehba; Gill, Harjot Singh; Galal, Ahmed M. (Case studies in thermal engineering, 2022)
The primary goal of this research is to examine the thermal variance in a dovetail fin under fully wet conditions with ternary hybrid nanofluid ZnFe2O4 +MnZnFe2O4 +NiZnFe2O4- H2O taking temperature and humidity ratio differences into account as driving forces for heat and mass transfer systems, respectively. The consequences of surface convection, radiation, and internally generated heat on the heat exchange of the fin have been taken into account. The mathematical modeling involves dimensionless transformation to convert the balanced energy equation to ordinary differential equation, and the problem is then solved numerically as well as analytically using the fourth-fifth order Runge-Kutta-Fehlberg's (RKF) methodology and DTM-Pade approximant. The significance of major thermal parameters such as radiation-conduction, wet factor, heat generation, and the ambient temperature variable on the temperature profile is explored graphically, contributing to an analysis of thermal performance. As the main outcome, ternary hybrid nanoliquid exhibits higher thermal response compared to mono and binary hybrid nanoliquid. Also, the thermal dispersion is higher for the lower values of wet parameter and radiative variable.